Meeting the Needs of Visiting In-Service EFL Teachers from China - Conway, C; Richards, H (AUT University; VUW, 2007)
Providing short term intensive professional development courses that successfully meet the needs of course participants can be a challenging task. This paper discusses a tailor- made programme for visiting overseas teachers to a New Zealand university. It presents the pedagogical principles underpinning the course, and the considerations and processes taken in designing the course to meet participants’ needs. The paper discuss the extent to which these needs were met on the course as well as looking at how the learning was applied once the teachers were in back in their teaching context in China. It concludes with the language teacher educators’ insights into establishing and meeting needs, the value of reflections and the effectiveness of learning transfer.